PEMBUATAN PUPUK ORGANIK PADAT DAN CAIR DARI LIMBAH PETERNAKAN GUNA MENDUKUNG PERTANIAN BERKELANJUT DI DESA AIR SATAN KECAMATAN MUARA BELITI KABUPATEN MUSI RAWAS - Betty Herlina; Teguh Karyono; Judo Laksono; Sadjadi; Zulhapi Utama Adlan; Syntia Dwi Agustina; Bagus Dimas Setiawan (Jurnal Masda, 2023)
Community service is one of the obligations to the community which is carried out in a programmed and planned manner. By empowering the community which is the target group, the service is carried out as a relationship between empowerment and the target that will be the goal of service. Air Satan Village in Muara Beliti District is one of the agricultural and livestock areas, especially cattle and goats in Musi Rawas Regency. This resulted in a large amount of waste from livestock manure that was abandoned around the stables. Farmers' insight into the importance of protecting the environment is expected to increase as their knowledge increases in the utilization of natural resources into organic fertilizer. Pemberdayaan has a direction to provide motivation to the target community with education, direct practice. The method used is the method of lectures and demonstrations to the public. This activity is carried out by providing material through counseling (power point media) and then conducting demonstrations/training so that this counseling has success, namely farmers have the knowledge and ability to make liquid and solid organic fertilizers from livestock waste which can be used to replace inorganic fertilizers. This success was measured by the contribution of farmers who were active in discussions during the demonstration process. The increase in knowledge and ability is expected to contribute to the application process in the field.